Acute Toxicity Study of Methanol Extract of Baobab (Adansonia digitata Linn) Fruit Shell Extract in Mice - Inna Muhammad Fannami; Sani Hyedima Garba; Wilson Oliver Hamman; Samaila Musa Chiroma (Mazandaran University of Medical Sciences, 2023)
Background: The natural origin of medicinal plants does not guarantee their safety, as there are no sufficient studies on the safety, efficacy, and toxicity to support their benefit claims.  Objectives: This study aimed at investigating the oral acute toxicity of Adansonia digitata L. (A. digitata) fruit shell extract in mice. Methods: The maceration method was employed for the extraction of the A. digitata fruit shell using methanol. The extract was then screened for its phytochemical constituents both qualitatively and quantitatively. Lorke's method was followed for the toxicity study, and the mice were observed for clinical signs of toxicity and mortality. Further, serum was analyzed for liver and kidney function biomarkers besides the histology of the liver, kidney, and cerebellum.  Results: No single death was recorded and no sign of toxicity persisted for more than 2 hours post-administration to the extracts up to 5000 mg/kg. Therefore, the - of A. digitata fruit shell is above 5000 mg/kg. Additionally, no changes were observed in the weights as well as the relative organ weight of the mice. Further, no statistically significant changes were seen in their liver and kidney function biomarkers, besides the relatively intact histological appearance of their liver, kidney, and cerebellum.  Conclusion: The oral acute toxicity of methanol extract of A. digitata fruit shell is above 5000 mg/kg; hence, it is relatively safe to use it for medicinal purposes. However, a longer study duration is recommended to evaluate its toxic effects on fertility, teratogenicity, and carcinogenic potentials.